THE BRAND AND ITS IMPACT ON THE POSITIONING OF THE ASOALIENU - Vergara Zurita, Heidy Elizabeth; Sandoval Gallegos, Mónica Gabriela; Guamán Dután, Manuel Elías (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
The objective of this study is to design the brand for the Nutriandina Entrepreneurs Food Production and Marketing Association (ASOALIENU), in the province of Chimborazo. The research is of documentary and field type, the deductive and inductive methods for collecting information through interviews, digital surveys applied in brand validation and graphic proposals that respond to the lack of positioning of the ASOALIENU Association in the market, As an object of study the PEA of the city of Riobamba with a sample of 381 people. 63.8% of people are unaware of the existence of the association, and 74.7% are willing to purchase the products they sell. Digital channels such as the website and social networks are the efficient means to position the brand with respect to the target audience, in order to inform, build loyalty and position the association through strategic planning. For the design the Bruce Archer methodology was applied with a structured, synthetic and functional result. The importance of design management is concluded for the creation of a brand that affects the positioning and strategic planning of the association.